Decompressive hemicraniectomy in supra-tentorial malignant infarcts - Nizami, Furqan A. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Decompressive hemicraniectomy not only reduces the intracranial pressure but has been demonstrated to increase survival and decrease the morbidity in patients with supratentorial malignant brain infarcts (STMBI). The aim of this study was to assess the efficacy of surgical decompression to decrease the mortality and morbidity in patients with STMBI refractory to medical therapy and to compare the results with those of the medically managed patients. METHODS: All the 24 consecutive patients with clinical and radiological diagnosis of STMBI, refractory to medical management in 2 years, were included. Option of surgical decompression after explaining the outcome, risk and benefits of the procedure was given to the attendants/relatives of all patients who were fulfilling the inclusion criteria. The patient group, whose attendants/relatives were not willing to undergo surgery, were subjected to the same medical therapy and they were taken as the “control group.” RESULTS: Supratentorial malignant infarcts were more common in the age group of 41–60 years. Mean age of presentation was 42.16 ± 16.2 years and the mean GCS on admission was 7.83 ± 2.1. Mortality was 16.7% in the surgically and 25.0% in the medically managed group. Patients operated early (<48 h), age ≤60 years, midline shift <5 mm and size of infarct less than 2/3(rd) of the vascular territory involved showed good prognosis. The functional outcome revealed by modified Rankin Score (mRS) and Glasgow Outcome Score (GOS) was better in surgically managed patients. Results of the Zung Self-Rating Depression Score were better in surgically managed patients at 1 year. Barthal Index in the surgically managed group showed statistically significant results. CONCLUSIONS: Decompressive hemicraniectomy with duroplasty if performed early in STMBI not only decreases the mortality but also increases the functional outcome when compared with patients who were managed conservatively with medical therapy only.